2021
DOI: 10.3390/biom11091324
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Region in the Common Amino-terminal Domain of Hendra Virus P, V, and W Proteins Responsible for Phase Transition and Amyloid Formation

Abstract: Henipaviruses are BSL-4 zoonotic pathogens responsible in humans for severe encephalitis. Their V protein is a key player in the evasion of the host innate immune response. We previously showed that the Henipavirus V proteins consist of a long intrinsically disordered N-terminal domain (NTD) and a β-enriched C-terminal domain (CTD). These terminals are critical for V binding to DDB1, which is a cellular protein that is a component of the ubiquitin ligase E3 complex, as well as binding to MDA5 and LGP2, which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(52 citation statements)
references
References 169 publications
(239 reference statements)
8
44
0
Order By: Relevance
“…This apparent conflicting behavior might arise from the much higher aggregation propensity of the HeV W protein that may hinder protease cleavage. This observation mirrors our previous studies where the HeV V protein was found to jellify under conditions where NiV V did not [82,83].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This apparent conflicting behavior might arise from the much higher aggregation propensity of the HeV W protein that may hinder protease cleavage. This observation mirrors our previous studies where the HeV V protein was found to jellify under conditions where NiV V did not [82,83].…”
Section: Discussionsupporting
confidence: 90%
“…In line with the ability of the HeV V PNT3 region, common to both the V and W proteins, to undergo a liquid-to-gel transition and to form amyloid-like fibers [82,83], we herein show that both the HeV and NiV W proteins form phase separated condensates that bind the amyloid-specific CR and ThT dyes.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The PNT3 3A variant shows a significant increase in the relative solubility compared to PNT3 HeV wt (Fig. 4A and 4B), a result in agreement with previous findings that pointed out a much lower propensity to form amyloid-like fibrils for PNT3 3A [25]. The three variants where only one Tyr was replaced, however, show no significant difference in the PEG1/2 values compared to HeV PNT3 wt (Fig.…”
Section: Aggregation Propensity Of the Eyyy Motif Pnt3 Variantssupporting
confidence: 91%